A SUMOylation Motif in Aurora-A: Implications for Spindle Dynamics and Oncogenesis - Pérez de Castro, Ignacio; Aguirre-Portolés, Cristina; Martin, Benedicte; Fernández-Miranda, Gonzalo; Klotzbucher, Andrea; G. Kubbutat, Michael H.; Megías, Diego; Arlot-Bonnemains, Yannick; Malumbres, Marcos (Frontiers in Oncology, 2011)
Aurora-A is a serine/threonine kinase that plays critical roles in centrosome maturation, spindle dynamics and chromosome orientation and is frequently found overexpressed in human cancers. In this work, we show that Aurora-A interacts with the SUMO conjugating enzyme UBC9 and co-localizes with SUMO-1 in mitotic cells. Aurora-A can be SUMOylated in vitro and mutation in the highly conserved SUMOylation residue lysine 249 results in the induction of mitotic defects characterized by defective and multipolar spindles. The Aurora-AK249R mutant has normal kinase activity but it displays altered dynamics at the mitotic spindle. In addition, ectopic expression of the Aurora-AK249R mutant results in a significant increase in the susceptibility to malignant transformation induced by the Ras oncogene and an increased protection against apoptosis in tumor cells treated with mitotic poisons. These data suggest that modification by SUMO residues may control Aurora-A function at the spindle and suggest that deficient SUMOylation of this kinase may have relevant implications in tumor development or cancer therapy.